2006
DOI: 10.1590/s1020-49892006000200003
|View full text |Cite
|
Sign up to set email alerts
|

Mortalidade por doenças cardiovasculares em três estados do Brasil de 1980 a 2002

Abstract: The decreases in weighted adjusted mortality rates from CDs, IHD, and CVD occurred after 1980, so it is unlikely that the declines resulted from controlling risk factors or from the practice of myocardial revascularization. The decreases might be related to a period of strong economic development preceding the declines, which translated into improved living conditions and reduced exposure to infections in the perinatal period and childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
17

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 21 publications
0
10
0
17
Order By: Relevance
“…Assim, em virtude da elevada porcentagem de óbitos por causas mal definidas observada para o triênio de 1989-1991, nas macrorregionais de saúde do Paraná, optou-se pela correção do número de óbitos por DCV seguindo a metodologia usada por Oliveira et al 1 DCV e nem para as variáveis socioeconômicas analisadas.…”
Section: Artigo Articleunclassified
See 1 more Smart Citation
“…Assim, em virtude da elevada porcentagem de óbitos por causas mal definidas observada para o triênio de 1989-1991, nas macrorregionais de saúde do Paraná, optou-se pela correção do número de óbitos por DCV seguindo a metodologia usada por Oliveira et al 1 DCV e nem para as variáveis socioeconômicas analisadas.…”
Section: Artigo Articleunclassified
“…cfm¿idxt=21377, acessado em 15/Jul/2011). No Estado do Paraná, em 2008, as DCV representaram 32,3% do total de óbitos; os coeficientes de mortalidade por infarto agudo do miocárdio e doenças cerebrovasculares foram, respectivamente, 44,1 e 60,7 óbitos por 100 mil habitantes 1 . Apesar de estudos mostrarem uma redução das DCV e de seus principais subgrupos (doenças isquêmicas do coração e doenças cerebrovasculares) desde os anos de 1970, o risco de morte por essas doenças ainda continua sendo maior em países subdesenvolvidos do que nos industrializados 2,3 .…”
Section: Introductionunclassified
“…Although some studies show a decrease in CVD deaths 1,[3][4][5][6][7][8]11,[19][20][21] , possibly due to accelerated economic development, bringing with it better living conditions and less exposure to infections during the perinatal period 4 , such deaths may present themselves in a non-homogeneous manner within the population groups of a given country, as mentioned by Frank et al 22 . Reinforcing these findings, Mansur et al 19 found an increase in the risk of death due to these diseases in the less developed states of the country, which agrees with the study by Farias et al 23 , which suggests that despite a decrease in recent years, these deaths may show different patterns in the different socioeconomic groups.…”
Section: Discussionmentioning
confidence: 99%
“…The nation has gone from high levels of infant mortality and a predominance of infectious and parasitic diseases, to higher mortality rates among those more advanced in age due to chronic, non-transmissible diseases and external causes 2 . In the last 60 years of the 20 th century, mortality due to all causes in Brazil dropped due to public health measures and preventive medicine techniques that, added to economic development, resulted in lower infant mortality and longer life-expectancy [3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, a redução de fatores de risco associados às DCV, como o consumo de tabaco, sedentarismo, uso de álcool, aliada à alimentação saudável e ao controle de hipertensão arterial, pode levar à redução da mortalidade por esse grupo de causas 7 . Embora estudos de tendência apontem para uma diminuição das DCV, principalmente em regiões desenvolvidas 8 12 . O procedimento pode ser resumido pela fórmula X c = X + M * X/(T -M), em que X é o número de óbitos pela causa específica DCV, DIC ou DCBV, M é o número de óbitos por causas mal definidas, T é o número de óbitos por todas as causas, e X c é o número compensado de óbitos pela causa específica.…”
Section: Introductionunclassified